The Effect of Main Spindle Speed of Z3050 X 16 (II) Radial Surving Machine on HSS TOOL Wear on The ASTM A36 Steel Process - Hutapea, Gumarang; Nurbaiti, Nurbaiti; Witanto, Yovan; Hoten, Hendri Van (UNIB Press, 2021)
Radial drilling machine is a machine that functions to make holes, enlarge holes, smooth the surface of holes and others. The purpose of this study was to determine the effect of variations in the main spindle speed and to determine the cutting parameters of drilling with variations in the main spindle rotation of the machine 250, 320, and 400 rpm. The drill bits used in this study are HSS (High Speed Steel) chisels with a size of 16 mm and the material used is ASTM A36 steel. The method used to determine the level of tool wear is to calculate the reduction in tool weight every 8 times drilling at each speed variation, namely 250, 320, and 400 rpm. The greatest tool wear occurs at the highest engine rpm speed at 400 rpm with a tool wear value of 0.07 grams and the lowest wear at 250 rpm with a wear value of 0.02 grams. The depth of cut is 8 mm. The cutting speed at 250 rpm got a value of 0.01256 m/min, the cutting speed at 320 rpm got a value of 0.0160768 m/min and at 400 rpm the value was 0.020096 m/min. The cutting time at 250 rpm was 0.16mm/minute, the cutting time at 320 rpm was 0.125 mm/minute, the cutting time at 400 rpm was 0.1mm/minute. The speed of producing fury at a speed of 250 rpm obtained a value of 10.048 cm3/minute, at a speed of 320 rpm a value of 12.861 cm3/minute was obtained, and at a speed of 400 rpm a value of 16.076 cm3/minute was obtained.